East is East?: Beyond the Global North and Global South in Criminology - Piacentini, Laura (The British journal of criminology, 2024)
This paper identifies an absence in currently constituted criminological discourse on the Global North and Global South. This absence is the Global East. The Global East is not a defined region but a relation of betweenness, geographically and geo-politically, within and between the South and North, representing peoples from countries and societies which fit imperfectly into a North/South binary. We focus on the Eastern European and Eurasian regions to demonstrate this point, concentrating specifically on its omission in punishment and society studies. Our paper makes a positive argument for the Global East concept, disrupting the assumed categories of North and South and producing a strategic essentialism to help better represent peoples thus far overlooked in southern criminology.